Simulation of biomass gasification in circulating fluidized bed reactor by aspen plus - Pinho, T. S. (2019)
Biomass is the fourth largest source of energy in the world. Many consider it to be the best option, with the greatest potential as an alternative energy supply which meets energy requiremen ts, for ensuring future fuel supply. Biomass energy resources are potentially the world's largest and most sustainable energy source, a renewable resource comprising 220 billion oven-dry tons (about 4500 EJ) of annual primary production [1]. lt is currently assumed that 5% of this energy could be mobilized to produce energy, i.e. a total of 225 EJ representing an energy equivalent ofmore than 5 billion tons ofoil equivalent, accounting for almost 50% ofthe world's total primary energy demand at present [2]. Hydrogen production is one of the most promising alternative energy technologies . The majority of experts consider that hydrogen has a significant role to play as an important energy carrier in the future energy sector [3]. Howe ver, it is a secondary form of energy that, like electricity, must be manufactured. A promising way to generate hydrogen is by thermochemical conversion of biom ass to synthe sis gas , consisting of a mixture of H2, CO, C0 2, CH.i, 0 2, N2 and tar. ln order to maximize H2 yield, an Or steam circulating fluidized bed (CFB) gasification process was proposed. For this purpose a computer simulation model was developed using the commercial chemical process simulator ASPEN Plus.